2011
DOI: 10.1089/thy.2010.0103
|View full text |Cite
|
Sign up to set email alerts
|

Urticaria and Thyroid Autoimmunity

Abstract: Background: Chronic urticaria is a common clinical condition whose etiology, in about 75% of cases, is unknown and is therefore called chronic idiopathic urticaria (CIU). A link between CIU and autoimmune thyroid diseases was proposed several decades ago. Here we review this topic. Summary: Several studies have been performed to determine if and to what degree there is an association between CIU and autoimmune thyroid diseases, particularly autoimmune thyroiditis. Many of these studies were not well controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 80 publications
1
47
0
2
Order By: Relevance
“…In general, urticaria is a very common skin disorder that can have immune, non-immune or idiopathic causes [9]. The idiopathic urticaria is accounted for in 75% of all urticaria cases [10]. Skin lesions appearing within a six-week period characterize acute urticaria, whereas chronic urticaria is defined as the presence of urticaria over a longer period of time.…”
Section: Introductionmentioning
confidence: 99%
“…In general, urticaria is a very common skin disorder that can have immune, non-immune or idiopathic causes [9]. The idiopathic urticaria is accounted for in 75% of all urticaria cases [10]. Skin lesions appearing within a six-week period characterize acute urticaria, whereas chronic urticaria is defined as the presence of urticaria over a longer period of time.…”
Section: Introductionmentioning
confidence: 99%
“…At least in a subset of patients, CSU has an autoimmune basis, as demonstrated by the presence of antibodies against the α-subunit of the high-affinity IgE receptor (Fc ε RI α ), or against IgE itself in the serum of 30%-40% of such patients (1)(2)(3). The association of CSU with thyroid autoimmunity further supports its autoimmune origin (4). CSU patients frequently suffer from Hashimoto's thyroiditis and increased serum levels of anti-thyroid antibodies were reported in 10% to 33% CSU patients (4,5).…”
Section: Sumáriomentioning
confidence: 90%
“…The association of CSU with thyroid autoimmunity further supports its autoimmune origin (4). CSU patients frequently suffer from Hashimoto's thyroiditis and increased serum levels of anti-thyroid antibodies were reported in 10% to 33% CSU patients (4,5). Coexisting Graves' disease (GD) has been reported less frequently than HT, with an estimated preva lence ranging from 1% to 4% (6).…”
Section: Sumáriomentioning
confidence: 91%
“…Our findings are consistent with these results. Another study carried out several decades ago proposed a link between chronic urticaria and autoimmune thyroid diseases, although the mechanisms of the apparent association between chronic urticaria and serological evidence of thyroid autoimmunity were not clear (48). A group of researchers has suggested that there could be a skin mast cell autoreactivity in HT patients, irrespective of autoreactive chronic urticaria (49).…”
Section: Discussionmentioning
confidence: 99%